(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Sports risk has become a threat to the sports sector in general and the impact on an efficient player and the old stadiums in particular. So have such a thing fertile ground of global insurance companies to exploit it optimally exploited through the development and marketing of insurance lids for the provision of protection for athletes of different risks they may face, which contributed to the growth and development of the performance of these companies and helped in the emergence of sports insurance specialist firms. And through the insurance process in the field of sports and where the insurance is a type of social solidarity. The main problem is this spirit manifested search in question is whether to embrace sports institutions sports insurance role in the development of the insurance industry.